THE MEANING OF TABOO WORDS FOUND IN 6IX9INES SONG LYRIC ON ALBUM "DUMMY BOY" - Made Manda Septikad Dewi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study discusses taboo words in the language used in song lyrics. In the song lyrics there are many taboo words, therefore the meaning in the word taboo is an interesting topic to be discussed in the field of linguistics, especially those related to taboo words. This study has a specific purpose that can be studied, namely to analyse the meaning of taboo words contained in taboo words. The purpose of this study is to contribute to the study of literature, especially those related to taboo words. The qualitative method used in this study was to analyse the data. The method is used to provide a clear analysis of the data according to the theory of Leech (1981). The results of this analysis, researchers find the meaning of the taboo word, namely the conceptual meaning and also the connotative meaning. The occurrence of conceptual meaning is dominantly for the use of taboo words in these song lyrics.